A qPCR-Based Method for Quantification of RCA Contaminants in Oncolytic Adenovirus Products - Gao, Menghan; Yngve, Erik; Yu, Di; Jin, Chuan (Frontiers in Molecular Biosciences, 2022)
Oncolytic adenovirus is one of the most promising treatments against cancer and is widely evaluated clinically. During high titer production, "Wild-type"-like replication-competent adenovirus (RCA) contaminants can be generated through recombination events due to the DNA sequence similarity between oncolytic virus and host cells. These RCA contaminants raise various safety concerns in clinics. Cell culture-based methods have been developed to detect RCA contaminants in replication-deficient adenovirus vectors based on the test cell line are permissive for the growth of RCA contaminants while non-permissive for the vectors. However, these methods are not suitable for distinguishing RCA contaminants from the oncolytic adenovirus products since both can replicate in test cell lines. Here, we reported a qPCR-based method to quantify RCA contaminants quickly and reliably in E1B-deleted oncolytic adenovirus products. This method is based on specific detection of the E1B gene, which can be acquired during production via recombination events between viral and host cell DNA. The assay is sensitive with the limit of detection at 10 VP of the RCA contaminants and the limit of quantification at 75 VP of the RCA contaminants in each 40 µL qPCR reaction. We have also validated the method on virus batches produced in the non-GMP and GMP conditions. Our results showed that this qPCR-based method was reliable and robust for detecting and quantifying RCA contaminants in oncolytic adenovirus products. The method may also be adapted for other oncolytic adenoviruses products by switching primer sets.